Analisis Kepuasan Konsumen Kacang Balado Cap Burung Cendrawasih UD. Monang di Pusat Oleh-oleh Khas Bali Hawai - JON ALPREDO MALAU; NYOMAN PARINING; A.A.A. WULANDIRA SAWITRI DJELANTIK (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2021)
Analysis of Consumer Satisfaction of Balado-flavor Peanut with the Trademark of Burung Cendrawasih of UD. Monang At the Balinese Typical Gift Shop of Hawai At present UD. Monang has produced four types of processed nuts. The four types of processed peanuts are kapri peanut, salted peanut, koro nut and balado-flavor peanut. Processed peanuts that have been produced are then distributed to shops, wholesalers, and souvenir outlets/gift shops in Bali. The results of research using the Importance Performance Matrix and CSI showed that consumer satisfaction was categorized as good, with a score of 0.6965 or 69.65%. The CSI value of balado-flavour peanut products with the trademark of Burung Cendrawasih was in the range of 0.61 - 0.80, which means that the satisfaction index meets the satisfaction criteria, but still requires improved performance so that the criteria for the consumer satisfaction index of the product become very satisfied, reaching 100%, or 1.0, while based on the importance performance matrix the assessment attributes are divided into four quadrants. In the first quadrant, there are no attributes that are the top priority, in the second quadrant, the attributes included are attributes of a reasonable price, flavor offered, product aroma, accuracy of packaging volume, cleanliness of product packaging and ease of obtaining products. Furthermore, in the third quadrant, the attributes included are packaging design, fulfillment of product benefits, brand popularity, and finally the fourth quadrant that includes only product packaging attributes.